Advances in research carried out on abaca crops established in Costa Rica with special reference to agroforestry systems - Araya-Salas, Mónica (2022)
Musa textilis also known as abacá, is a non-timber forest product that produces a natural fiber extracted from the pseudostem of the plant. It’s an export crop and its production is in the hands of small producers. The management of this crop at the farm level is compatible with the biodiversity, decarbonization and bioeconomy policies and strategies promoted by the country’s government authorities. In particular, this work presents crop diversification alternatives to support the reduction of deforestation, forest management and conservation, reforestation and the promotion of agroforestry systems (SAF). It also has an impact on the conservation of biodiversity, water, scenic beauty values in the rural landscape and stimulates the economy. The problem being addressed is the lack of scientific and technological knowledge on the aspects related to the abaca cultivation, including agroforestry systems with commercially valuable timber species, as well as the characterization of the fiber to propose new uses and add greater value to the export product and open up new ventures at the national level.